2016
DOI: 10.4018/978-1-4666-9932-8.ch006
|View full text |Cite
|
Sign up to set email alerts
|

Use of Community of Practice Dimensions in Community-Based Teacher Professional Development

Abstract: The role of communities of practice (CoPs) in teacher professional development (TPD) is increasingly recognized. CoPs help teachers in a cohort to reflect on their practices, develop new skills and find motivation through mutual collaboration. With the affordances provided by Web technologies, the potentiality of online CoPs as a means of improving (TPD) has become a reality and is gaining popularity as the flexibility provided help teachers improve their instructional practices. The Online Continuing Professi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
1
1
0
1
Order By: Relevance
“…In order not to lose face, participants may adopt an avoidance strategy when teachers are watching. This finding correlates with the findings in Murugaiah et al (2016) as they reported that Malaysian students decreased their online participation to avoid potential conflicts and to save face. However, effective learning sometimes involves risk-taking, which requires students to shoulder more responsibilities and teachers to empower students with space to grow in learning (Carless, 2012).…”
Section: Benefits Of the Teacher's Presencesupporting
confidence: 81%
See 1 more Smart Citation
“…In order not to lose face, participants may adopt an avoidance strategy when teachers are watching. This finding correlates with the findings in Murugaiah et al (2016) as they reported that Malaysian students decreased their online participation to avoid potential conflicts and to save face. However, effective learning sometimes involves risk-taking, which requires students to shoulder more responsibilities and teachers to empower students with space to grow in learning (Carless, 2012).…”
Section: Benefits Of the Teacher's Presencesupporting
confidence: 81%
“…In a high-context and collectivistic culture, individuals tend to use more indirect, mutual face-saving behavior in communication (Murugaiah, Thang, Azman & Nambiar, 2016). In order not to lose face, participants may adopt an avoidance strategy when teachers are watching.…”
Section: Benefits Of the Teacher's Presencementioning
confidence: 99%
“…Lave e Wenger (1991apud GUDOLLE et al, 2012) assumem a aprendizagem como algo que surge da participação dos sujeitos em comunidades de prática e a caracterizam com três critérios: Domínio, onde a comunidade é formada de pessoas com um interesse e dedicação compartilhada em relação a uma prática; Comunidade, onde os membros realizam atividades conjuntas, discutem, se ajudam, compartilham informações; Prática, pois não se trata apenas de interesse por um tópico, mas na dedicação empregada no realizar atividades naquela área. Notamos que, apesar da Comunidade de Prática não estar estritamente relacionada com o contexto educacional, o seu campo teórico está registrado em estudos sobre a formação de professores (MURUGAIAH et al, 2016).…”
Section: Comunidades No Contexto Educacionalunclassified